Communicating Biotechnology: Relationships Between Tone, Issues, and Terminology in U.S. Print Media Coverage - Jefferson D. Miller; Mamane Annou; Eric J. Wailes (Journal of Applied Communications, 2003)
As part of a nationwide study on the public acceptability of agricultural biotechnology, researchers performed a content analysis on two years of print news coverage of biotechnology (2000-2002). Qualitative analysis methods included examining text from selected national newspapers, regional newspapers, and trade publications for common issues, tone, and terminology. A team of three coders, trained to an acceptable level of agreement (Cohen’s K = .80), examined and coded the articles. The relationship between the tone of the article and the terminology used in reference to biotechnology (e.g., “genetically engineered,” “genetically modified,” or “biotechnology”) has practical applications for both public relations practitioners and communication researchers. “Biotechnology” was associated with the largest percentage of articles with positive tones. “Genetically modified” was associated with more neutral articles. “Genetically engineered” was the term of choice for authors of physical science articles, which were mostly positive. Understanding these relationships may help communication practitioners choose their terminology to achieve their communication goals, as well as opinion researchers, who, in developing survey instruments, may wish to choose a term that carries the least amount of bias.